Digestion characteristics of grains and flours for breads of low glycaemic potency : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Palmerston North, New Zealand - Srinivasagam Ramasamy Venkateswaran, Akila (Massey University, 2020)
In a survey of supermarket breads containing grain particles in New Zealand it was evident that grain structure reduced the starch digestibility of the breads, but the effect was small unless the inclusion rate of the large grain particles (>1 mm) was high (65% or more). The factors that influenced starch digestibility and glycaemic potency of grain particles of various sizes were studied in this research. It was shown that relatively large particle size and incomplete gelatinization of starch in the grains studied make them more resistant to digestion than others. From the knowledge gained in preliminary research, a range of kibbled (large grain particles) grain breads was developed containing 75% of large (> 2.8 mm) grain particles. The digestibility of starch in the prototype kibbled grain breads was examined 𝘪𝘯-𝘷𝘪𝘵𝘳𝘰 by simulated small intestinal digestion either with the grains intact or after homogenizing the breads. The results showed that the glycaemic potency of kibbled grains bread was low in comparison to white breads provided that the grain particles remained intact. However, when the kibbled grain breads were completely homogenized to eliminate grain structure the estimated glycaemic index (GI) increased by 31% and was similar to that calculated for white bread. An 𝘪𝘯-𝘷𝘪𝘷𝘰 study was conducted to compare the 𝘪𝘯-𝘷𝘪𝘵𝘳𝘰 estimates of glycaemic potency with the 𝘪𝘯-𝘷𝘪𝘷𝘰 findings and showed that the results from the 𝘪𝘯-𝘷𝘪𝘷𝘰 and 𝘪𝘯-𝘷𝘪𝘵𝘳𝘰 studies were highly correlated. This showed that endosperm structure played a significant role in reducing the glycaemic potency of the breads but only when the grain particles were large (>2.8 mm) and when they were swallowed intact. This suggested that the glycaemic potency of breads cannot be significantly reduced by adding high proportions of large grain particles as chewing reduces particle size and destroys much of the endosperm structure that would restrict digestion of the unchewed grain particles. Hence, increasing the proportion of large grain particles in bread is, in itself, ineffective in reducing the rate of starch digestion and consequently, blood glucose response 𝘪𝘯-𝘷𝘪𝘷𝘰. However, in all cases, it was found that adding large grain particles to breads made in this work or sourced commercially increased the proportion of non-starchy ingredients (mostly insoluble and soluble fibre) so reducing the proportion of available starch for digestion, in the bread. The 𝘪𝘯-𝘷𝘪𝘵𝘳𝘰 results showed that reducing the proportion of available starch in the bread, either by increasing the proportion of whole-grain particles or by increasing the proportion of fibre or protein added to the breads is an effective strategy to reduce the glycaemic potency of breads. As expected from the earlier experiments, the glycaemic potency of the carbohydrates (GI) present in these breads was similar to that of a standard commercial white bread. Therefore, reducing the proportion of carbohydrate in bread formulations by increasing the proportion of protein and/or fibre is an effective strategy for reducing glycaemic potency of breads even though the glycaemic index, which shows the relative glycaemic potency of the available carbohydrate portion of the bread, is unchanged.
Figures 2.5 (=Lopez-Rubio et al., 2008 Fig 2 & Damager et al., 2010 Fig 2) and 2.6 (=Kim et al., 2012 Fig 5) were removed for copyright reasons. Modified copyrighted Figures remain for clarity's sake.
Keywords: Bread; Grain in human nutrition; Carbohydrates in human nutrition; New Zealand; Digestion; 300607 Food technology